Pendampingan Peningkatan Kualitas Produk Tradisional Dalam Meraih Pangsa Pasar Komoditi Lokal : Desa Wirotaman, Ampelgading, Kabupaten Malang - Agus Wiastono; Wiwit Setyo Wardani; Koslani; Jassica Aulia Virginia; Marlince Kobu Banya; Sisilia Nanga (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Product quality is one of the important components in a production process for products to be sold by the company. The problem of product quality is very influential on the value of market share. The purpose of this paper is to determine the importance of product quality to increase market share in order to gain profits for the company. The data analysis used in this paper is descriptive qualitative by utilizing sources from journals, books, and articles which are previous studies then read and processed first so that they become research material. The result of the discussion of this paper is that product quality affects the level of consumer satisfaction so that it will increase consumer loyalty and the resulting product provides benefits for the company. In this case, product quality can be said to influence consumers in making purchasing decisions. Therefore, the quality of the product must be of high quality so that it can be said to be a good weapon to compete with the products of other companies.